Structure and tensile properties evaluation of samples produced by Fused Deposition Modeling - Gajdoš Ivan (Open Engineering, 2016)
This paper presents the result of a study evaluating the influence of alternative path generation strategy on structure and some mechanical properties of parts produced by Fused Deposition Modeling (FDM) technology. Several scientific investigations focused on resolving issues in FDM parts by modifying a path generation strategy to optimize its mechanical properties. In this study, an alternative strategy was proposed with the intention of minimizing internal voids and, thus, to improve mechanical properties. Polycarbonate samples made by this alternative path generation strategy were subjected to tensile strength test and metro-tomography structure evaluation. The results reveal that the structure observed on build models differs from a structure expected from path generation predicted by software Insight 9.1. This difference affected the tensile strength of samples.